Higher education, stakeholder interface and teacher formation for church schools. (November 2019) - Stuart-Buttle, Ros
Church-affiliated universities operate with increasingly complex roles and functions when engaging with multiple stakeholders in the provision of higher education. This article asks how to understand and analyse the interactions when these universities are among the multiple stakeholders in Christian teacher education. What frameworks of analysis or tools of evaluation can be employed? Stakeholder theory is shown to support the identification of various community interests and involvements and enable clarification of whose perspective or priorities are to be taken into account. From a recent UK research case study, the need for greater understanding and management of stakeholder interests and activity within Christian teacher education is highlighted.